Changing the school: students' point of view about educational innovation - Sara Mori; Elettra Morini; Francesca Storai (IUL Research)
Rethinking teaching-learning model is one of the central topics in the debate on school systems. The Avanguardie Educative Movement gathers schools from all over the national territory that share practices based on a model with students actively participating in their educational path, aiming at promoting meaningful learning. The research aims to investigate how these schools have interpreted the concept of educational innovation and, in particular, the paper focuses on the results of the student questionnaire and of the psychometric tests administered to 1880 students from 52 schools who have been participating in the Movement experimentation for at least two years. The results show a positive association between the perceived level of innovation and the satisfaction with the functioning of the school. Students with high score on these dimensions also have high results in tests that investigate student satisfaction with school experience and daily organization of the study.